Ratio of CD68/CD163 in Breast Carcinoma with and without Axillary Lymph Node Metastatic - Wiratama, Priangga Adi; Sandhika, Willy (Folia Medica Indonesiana, 2020)
Tumor and its microenvironment can interact each other. Macrophage is part of tumor microenvironment. New drugs targeting specific superficial receptor of macrophage or cytokine of macrophage polarization have been found. Therefore, macrophage phenotype and its ratio of M1/M2 macrophage need to be identified. This identification could lead us to prognose breast cancer and monitor its therapy. Analytical observational study with cross sectional approach, conducted on paraffin block sample of breast carcinoma from Anatomical Pathology Laboratory of Dr. Soetomo General Hospital. The samples divided into four groups based on nodal metastasis staging (N0, N1, N2, and N3) and stained with antibody against CD68 and CD163. The ratio of CD68 and CD163 were analyzed with Anova test. There were difference expression of CD68 as M1 macrophage marker in various axillary node metastasis groups (p=0.015). There were difference ratio of CD68 as M1 macrophage marker and CD163 as M2 macrophage marker in various axillary node metastasis groups (p=0.005). There were difference ratio of macrophage M1 and macrophage M2 between N0 and N3 group, N2 and N3 group also.